Understanding the influence and effectiveness of applying the Customer management system on Foodpanda Bangladesh - Raisa, Fabeha (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.